G4D - a treasure hunt game for novice programmers to learn debugging - Venigalla, Akhila Sri Manasa; Chimalakonda, Sridhar (Smart learning environments, 2020)
Visual Programming Environments (VPEs) are predominantly being used to teach programming concepts through interactive games with interesting narratives. Games have been developed to teach basic concepts of programming such as deriving logic, writing code, debugging the code and so on. Debugging code is one of the most important activities that can improve the skill of tackling a problem. In programming, one needs to identify the correct location of an error and fix it, which is usually learned through experience. Games have been developed to teach debugging to novice programmers. Syntactical errors occur frequently in the early stages of programming. The existing debugging games aim to support users in debugging the logic of the problem, but do not target on correcting the code snippets based on syntax. To address this challenge of providing syntactical support, we propose a treasure hunt based debugging game, in which users pass through various levels of the game by debugging code snippets written in C language. We have evaluated G4D based on MEEGA+ model, with 20 volunteers, having different programming backgrounds. The results of the user survey indicate that G4D has a good quality level and about 75% of the volunteers have either strongly agreed or agreed to recommend G4D to their colleagues.